The Effect of Fat Emulsion on Hemodynamics Following Treatment With Propranolol and Clonidine in Anesthetized Rats. (November 2014) - Macala, Kimberly; Tabrizchi, Reza; O'Neil, Brian
Abstract Objectives There is evidence indicating that intravenous fatty emulsion (IFE) is beneficial in restoring circulatory function in certain types of drug overdose. The authors investigated the hemodynamic effects of IFE compared to epinephrine in rats treated with propranolol and clonidine. Methods Anesthetized male Sprague‐Dawley rats were instrumented for measurement of hemodynamics. Rats were randomly assigned to one of six groups (n = 6–8), and each received a clonidine infusion (150 μg/kg) or an equivalent volume of normal saline (0.9% NaCl) over 1 hour. Each rat then received normal saline (1.0 mL/kg) or propranolol (15 to 20 mg/kg). Thereafter, each rat received a dose of IFE (20% solution; 1.0 mL/kg) or epinephrine (2.0 μg/kg) or an equivalent volume of normal saline (1.0 mL/kg). Results Propranolol alone or with clonidine significantly (p < 0.05) reduced a number of hemodynamic parameters (mean arterial pressure, 37% to 70%; heart rate, 30% to 51%; cardiac contractility [dP/dtmax], 50% to 67%; and abdominal aortic blood flow, 50% to 83%), while increasing PR intervals (65% to 85%) and QTc intervals (26% to 64%). Saline and epinephrine treatment after propranolol and clonidine combined resulted in no survivors in saline and two out of six in epinephrine group. IFE resulted in significant survival (seven out of eight) for 30 minutes in rats treated with propranolol alone, and propranolol combined with clonidine (seven out of eight). Conclusions These data demonstrate that IFE is effective for resuscitating rats overdosed on propranolol combined with clonidine. The effect of IFF is unlikely due to a direct positive inotropic or chronotropic action on the myocardium. IFE is also more effective than epinephrine treatment in this paradigm.